Korean Wave and Fanaticism in an Islamic Perspective, and Their Influence on Student Behavior in the Era of Society 5.0 - Kania Azzahra Putri; Muhammad Rifqi Ibrahim; Rashel Dika Azzahra; Siti Nuraeni Azzahro; Giani Adzkia (Higher Education Spiritual Pedagogies, 2023)
This study aims to determine the effect of the Korean wave on the behavior of Indonesian University of Education students and to find out the Korean wave and fanaticism in an Islamic perspective. The research method used in this research is survey method and literature review. This research activity was carried out in two stages, first the author reviewed the existing and relevant literature to the research and then analyzed it, then the author collected survey data whose respondents were students of the Indonesian University of Education, this survey was carried out by distributing questionnaire links (Google Forms). The results showed that the Korean Wave had a significant influence on student behavior. On the one hand, there are positive impacts such as increasing interest in learning Korean culture, improving Korean language skills, and increasing motivation in learning foreign languages. However, negative impacts were also found, such as excessive fanaticism, neglect of local culture, and dependence on Korean content which disturbed the balance of daily life. Furthermore, this study explores an Islamic perspective related to the phenomenon of fanaticism that appears in the Korean WaveTherefore, this study also emphasizes the importance of awareness and understanding of Islamic teachings in dealing with the influence of the Korean Wave.